MAKNA BADIK BAGI MASYARAKAT SUKU BUGIS (Studi di Kelurahan Pulau Kijang, Kecamatan Reteh, Kabupaten Indragiri Hilir) - Ruwaidah "; Yusmar Yusuf (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2018)
Badik is a tradiotanal weapon of Bugis tribe. Bugis society believes bringing Badik can bring authority and helpes in a very urgent situation. When wanting to travel far, the man Bugis tribe who believe in the strength of Badik reluctant to leave Badik, as much as possible Badik it will be brought with him. In this case is certainly a controversy of the Indonesian Law with the belief of the community against customary tradition’s including in it the traditonal weapon Bugis tribe Badik or Kawali. Both have an equally strong position in society. With very clear Indonesian Law prohibits individual’s carrying sharp weapon’s, but for the community of Bugis is a protector for him. the theory used is the theory of Symbolic Interactionisme by George Herbert Mead.Data analysis was done by descriptive method with qualitative approach, the data collecting technique in the research was purposive where the respondent is 7 people consisting of the elder and the ordinary people who have Badik aged 30 years above. From the results of the research in the field, it is known that the social function of Badik for the tribe of Bugis in the urban village of Kijang, the subdistrict of Reteh, the downstream Indragiri Hilir, that is the identity of the Bugis man to maintain the self – esteem (siri). The strength of the Badik comes from the old iron which has long been believed to have magical powers that can affect the condition, the state of the owner. The beliefs of the Bugis tribe people against Badik are still attached to this day, but the public understanding of the symbol’s found in Badik has been reduced.Kata Kunci:Meaning , Badik, Bugis Tribe.